The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.17275/per.20.27.7.2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Students’ Misconceptions of Astronomy Through Concept Cartoons

Abstract: The purpose of the study was to diagnose students’ misconceptions of a number of basic astronomy concepts, namely, the Universe, the Sun, Comets and Constellations. The study was designed as a mixed method research and the sample was composed of a total of 110 seventh grade students. Data were collected through concept cartoons and interviews. In the concept cartoons prepared for each concept, there were four expressions, one of which is a scientific judgment, while the others were misconceptions. Students wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 44 publications
3
9
0
4
Order By: Relevance
“…In terms of size, it was observed that most small samples of 50-100 people were used. In general, the studies conducted in the field of education in Turkey is known to take place in small YYÜ Eğitim Fakültesi Dergisi (YYU Journal of Education Faculty), 2021;18(1)622-651,http://efdergi.yyu.edu.tr, doi:10.33711/ yyuefd.919438 Araştırma Makalesi ISSN: 1305-2020 647 samples (Arik and Turkmen, 2009;Meteors et al, 2012;Selcuk, Palanci, Kandemir and Dundar, 2014;Yalcin, Yavuz and Dibek, 2016).…”
Section: Findings Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of size, it was observed that most small samples of 50-100 people were used. In general, the studies conducted in the field of education in Turkey is known to take place in small YYÜ Eğitim Fakültesi Dergisi (YYU Journal of Education Faculty), 2021;18(1)622-651,http://efdergi.yyu.edu.tr, doi:10.33711/ yyuefd.919438 Araştırma Makalesi ISSN: 1305-2020 647 samples (Arik and Turkmen, 2009;Meteors et al, 2012;Selcuk, Palanci, Kandemir and Dundar, 2014;Yalcin, Yavuz and Dibek, 2016).…”
Section: Findings Discussion and Conclusionmentioning
confidence: 99%
“…Ancak araştırmacılar arasında ilgi gören çalışma konuları zamanla çalışmaların birbirine benzer özellikler göstermesine ve alan yazının kendini sürekli tekrar etmesine neden olabilmektedir (Deng, Chen, Tsai ve Chai, 2011;Lederman, 2007). Bunun önüne geçebilmek için, YYÜ Eğitim Fakültesi Dergisi (YYU Journal of Education Faculty), 2021;18(1)622-651,http://efdergi.yyu.edu.tr, doi:10.33711/ yyuefd.919438 Araştırma Makalesi ISSN: 1305-2020 626 ülkemizin bu çalışma alanında nerede bulunduğunu, kaydettiği aşamaları ve izlediği yöntemleri bilmek gereklidir. Bunun için bu çalışmada, Türkiye'de fen eğitimi alanında kavram karikatürü kullanımını konu makalelerdeki eğilimleri belirlemek amaçlanmıştır.…”
unclassified
“…Kavram karikatürlerinin alanyazında kavramsal anlamayı geliştirmeye, kavramsal değişime, kavram yanılgılarını ortaya çıkarmaya ve gidermeye (Atasoy ve Ergin, 2017;Atasoy, Tekbıyık ve Gülay, 2013;Balım, Deniş Çeliker, Türkoğuz, Evrekli ve İnel Ekici, 2015;Cinar ve Bayraktar, 2014;Ekici, Ekici ve Aydın, 2007;Çil, 2014;Minárechová, 2016, Ozdemir, Coramik ve Urek, 2020Serttaş ve Türkoğlu, 2020;Taşlıdere, 2013;Türkoğuz ve Cin, 2013), öğrencilerin epistemolojik inanışlarını anlamaya (Atasoy, 2020), yapılandırmacı öğrenme kuramının sınıflarda etkili uygulanmasına (Kabapınar, 2005;Keogh ve Naylor, 1999;Kinchin, 2004;Naylor ve Keogh, 1999a;Sasmaz-Oren ve Meric, 2014), biçimsel (formative) değerlendirmeye (Chin ve Teou, 2009Ormancı ve Şaşmaz-Ören, 2011;Uzoğlu, Yıldız, Demir ve Büyükkasap, 2013), probleme dayalı öğrenmeye (Balim vd., 2014;Balım, İnel-Ekici ve Özcan, 2016;İnel ve Balım, 2013;Kaçar, Ormanci, Özcan ve Balim, 2020;Oluk ve Özalp, 2007), argümantasyon sürecine (Çinici vd., 2014;Naylor, Keogh ve Downing, 2007;Webb, Williams ve Meiring, 2008), bilimin doğasını öğrenmeye (Çil ve Çepni, 2016), bilimsel süreç becerilerini geliştirmeye (Türkoğuz ve Cin, 2014), fen konularında farkındalık oluşturmaya (Aydın, 2015;Naylor ve Keogh, 1999b), akademik başarıya (Balım, İnel ve Evrekli, 2008;Baynazoğlu ve Atasoy, 2020;Yilmaz,...…”
Section: Kavram Karikatürleri Ve Sbkunclassified
“…Literatürde kavram karikatürlerinin "okuma becerilerinin gelişmesi (Demetrulias 1982), kelime dağarcığının gelişmesi (Goldstein 1986), problem çözmeyi sağlama (Jones 1987), düşünme becerilerini geliştirme (De Fren 1988), motivasyonu arttırma (Heintzmann 1989), çatışmaları çözmek (Naylor & McMurdo 1990), bilimsel bilgileri ortaya çıkarmak için (Guttierreze & Ogborn 1992, akt: Keogh & Naylor, 1999, fen kavramlarına yönelik olumlu tutum geliştirme (Sahin vd., 2015) ve değerlendirme amaçlı (Ormancı & Şaşmaz Ören, 2011) kullanıldığı görülmektedir. Kavram karikatürleri ile ilgili yapılan çalışmalar incelendiğinde, kavram karikatürlerinin kavram yanılgılarını belirleme ve gidermede etkili olduğu tespit edilmiştir (Atasoy & Ergin, 2017;Atasoy, Tekbıyık & Gülay, 2013;Kabapınar, 2005: 135;Keogh & Naylor, 1999;Kuşakçı-Ekim, 2007;Serttaş & Yenilmez Türkoğlu, 2020;Stephenson & Warwick, 2002).…”
Section: Kavram Yanılgıları Ve Kavram Karikatürüunclassified